Global vaccine confidence trends among adults above and below age 65 - Bei Liu; Xiyu Zhang; Yongqiang Lai; Tao Sun; Chao Wang; Tianshuo Zhao; Sihui Zhang; Baoguo Shi; Ye Li; Fuqiang Cui (npj Vaccines)
Abstract This study is interested in global vaccine confidence because it directly impacts vaccination rates and public health outcomes, especially during the COVID-19 pandemic. Furthermore, due to the unique vulnerabilities to vaccine-preventable diseases, misinformation, and access to health information among adults aged 65 and older, understanding vaccine confidence in this population is crucial for developing targeted interventions and improving vaccination rates. The current research is limited by single-country surveys and cross-sectional designs, providing limited insights into these issues. We compared the vaccine confidence between the population over 65 and under 65 in terms of vaccine safety, effectiveness, compatibility with religious beliefs, and importance to children. We employed a hierarchical logistic model, and compared human development index (HDI) values to investigate determinants of vaccine confidence. Vaccine confidence increased between 2015 and 2019, but decreased between 2019 and 2022 across most global regions, exhibiting an inverted U-shaped trend. Population over 65 in high-income countries was more likely to agree on the safety, effectiveness, importance to children, and compatibility of vaccines with religious beliefs than those under 65, with agreement levels exceeding 80% for most aspects. Gender, education, income, and religion influenced vaccine attitudes among adults aged 65 and older. Countries with an HDI exceeding 0.9 consistently demonstrated positive trends in vaccine confidence. This relationship between HDI and vaccine confidence underscores the importance of comprehensive societal development in shaping attitudes toward vaccination. These findings can help develop targeted interventions and policies to improve vaccination rates among older adults.